2023
DOI: 10.1021/acs.orglett.3c01350
|View full text |Cite
|
Sign up to set email alerts
|

Mn(I)-Catalyzed Preferential Electrophilic C3-Maleimidation in Quinoxaline Leading to Spirocyclization and Dehydrogenation of Succinimides

Abstract: A Mn(I)-catalyzed site-selective nondirected C3maleimidation of quinoxaline is established. Herein, the electrophilic C3-metalation precedes over the o-directed strategy to access diversely substituted quinoxaline-appended succinimides. The products undergo PIFA-promoted C(sp 2 )−C(sp 3 ) spirocyclization via π-electrons drifting from aryls and Selectfluor-mediated dehydrogenation of succinimide at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The products were isolated in 62–95% yield. Further in 2023 Ghosh et al 34 reported a two-step approach to afford the spirocycles 151 by an initial Mn-catalyzed C-3 maleimidation of 2-arylquinoxalines 150 followed by spirocyclization in the presence of PIFA in DCM at room temperature (Method 2, Scheme 37).…”
Section: Heterocycle Directed Spirocyclizationmentioning
confidence: 99%
“…The products were isolated in 62–95% yield. Further in 2023 Ghosh et al 34 reported a two-step approach to afford the spirocycles 151 by an initial Mn-catalyzed C-3 maleimidation of 2-arylquinoxalines 150 followed by spirocyclization in the presence of PIFA in DCM at room temperature (Method 2, Scheme 37).…”
Section: Heterocycle Directed Spirocyclizationmentioning
confidence: 99%
“…In spite of significant progress in this area, the development of synthetic methods using inexpensive and environmentally benign catalysts is still desirable. Inspired by Song’s, 11 Wang’s 12 and Patel’s 13 work on manganese-catalyzed C2-hydroalkylation of indoles and imidazopyridines, we envisioned that selective ortho -hydroalkylation of aryl-substituted N -heteroaromatic compounds with maleimides could be accomplished using a cheaper, environmentally benign manganese catalyst. In continuation of our interest in transition-metal-catalyzed C–H functionalization of heterocycles, 14 herein, we disclose a manganese-catalyzed ortho -hydroalkylation­ of aryl-substituted N -heteroaromatic compounds­ with maleimides to produce 3-(2-( N -hetero­aryl)aryl)pyrrolidine-2,5-diones (Scheme 1b ).…”
Section: Table 1 Selected Conditions For Optimization O...mentioning
confidence: 99%
“…Notably, the largest and most diverse family of organic compounds comprises heterocyclic compounds. In this domain, nitrogen, nitrogen–sulfur, and nitrogen–oxygen-containing heterocycles, such as quinoxaline, benzothiadiazole, benzoxadiazole, and benzothiazole are prevalent structural motifs that present in numerous natural products, pharmaceuticals, and functional materials, particularly in photoluminescence areas, such as solar cells, dyes, pesticides, and organic synthesis. , Over the past few years, different research groups have established several functionalizations at the C-3 position of quinoxaline and the C-2 position of benzothiazole (Figure a-b) . However, limited research reports on C-4 functionalization of benzothiadiazole and benzoxadiazole have been published so far (Figure c) …”
mentioning
confidence: 99%